Mobile augmented reality application in medical education in the 2010s - Shook, Chin Yap; Rahmita Wirza Rahmat,; Siti Khadijah Ali, (Penerbit Universiti Kebangsaan Malaysia, 2021)
In the recent years, medical education is facing various difficulties. Students are struggling to visualize the internal organs and bones, it is insufficient cadaver for dissection demonstration, there are lack of equipment for training, and not enough opportunity for hands-on training. Technologies have been utilized to supplement teaching in medical education to overcome the mentioned difficulties. Augmented Reality in particular mobile Augmented Reality has shown a rise in the application of medical education in this decade. This paper aims to do a narrative review to study the overall progress and development of mobile Augmented Reality application in medical education from year 2010 to 2020. From the review done, we found that the application of mobile Augmented Reality in medical education is feasible, it is well accepted by medical students. We also identified current research gaps and potential future development of mobile Augmented Reality in medical education. It was found that there is lack of research done to study long term effect on the users. Interaction between virtual object and real-world object was lacking in some applications. More refinement and update are needed on flow, media and design of Augmented Reality application. There is also essential to study the influence of marker size or surface material.